A historical review of aggregation‐induced emission from 2001 to 2020: A bibliometric analysis. Issue 1 (3rd January 2022) - Xia, Qiming; Zhang, Yiyin; Li, Yiling; Li, Yirun; Li, Yixuan; Feng, Zhe; Fan, Xiaoxiao; Qian, Jun; Lin, Hui
Abstract: Aggregation‐induced emission (AIE) is a photophysical phenomenon that a certain group of luminescent materials that become highly luminous when aggregated in a bad solvent or solid state. This year is the 20th anniversary since the AIE concept firstly proposed in 2001. Many advanced applications were gradually being explored, covering optics, electronics, energy, and bioscience and so on. At present, bibliometrics can enlighten the researchers with comprehensive sights of the achievements and trends of a specific field, which is critical for academic investigations. Herein, we presented a general bibliometric overview of AIE covering 20 years of evolution. With the assistance of Web of Science Core Collection database and several bibliometric software tools, the annual publication and citation, most influential countries/regions, most contributing authors, journals and institutions, second near‐infrared (NIR‐II) related hotspots, as well as the forecast of frontiers were demonstrated and systematically analyzed. This study summarizes the current research status in AIE research field and provides a reference for future research directions. Abstract : A bibliometric analysis is conducted to overview the development of AIE in the past two decades and provides a unique perspective for this field. Researchers with high citations, keyword co‐occurrence networks, NIR‐II imaging related foamtree, and frontier perspectives on AIE are visualized via different software in this study. A multi‐interdisciplinary system has been formed with aggregate science as the core subject.